2018
DOI: 10.1177/1098612x18789549
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered surgical repair of a chronic oronasal fistula in a cat using autologous platelet-rich fibrin and bone marrow with a tailored 3D printed implant

Abstract: Clinical summary: A tissue engineering approach was used to aid the surgical repair of a chronic oronasal fistula (ONF) in a 13-year-old cat. A three-dimensional (3D) printed mesh, tailored to the size and shape of the ONF, was created to support a soft tissue flap used to close the defect; and also to provide a matrix for mesenchymal stromal cells present in bone marrow aspirate and bioactive cytokines and growth factors present in platelet-rich fibrin harvested from the patient. A CT scan at day 75 after sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…For animal surgery, Carla [ 133 ] conducted a surgical therapy of a chronic oronasal fistula in a cat using autologous platelet-rich fibrin and bone marrow loaded printed PCL scaffold. A CT scan revealed complete healing after a six-month follow-up.…”
Section: Pcl-based Composite Scaffolds Utilized In Different Situationsmentioning
confidence: 99%
“…For animal surgery, Carla [ 133 ] conducted a surgical therapy of a chronic oronasal fistula in a cat using autologous platelet-rich fibrin and bone marrow loaded printed PCL scaffold. A CT scan revealed complete healing after a six-month follow-up.…”
Section: Pcl-based Composite Scaffolds Utilized In Different Situationsmentioning
confidence: 99%
“…Several authors have used a centrifugation process at 3000 rpm to produce PRF from human patients (Hartshorne & Gluckman, 2016b; Sam, Vadakkekuttical, & Amol, 2015; Zumarán et al, 2018). The same centrifugation was also employed to produce PFR in a feline case report (Soares et al, 2018). Based on g‐force and centrifugation duration, the platelet‐rich fibrin constructed may differ in consistency, from gel‐like substance to a dense fibrin membrane (Arnoczky & Sheibani‐Rad, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Cats present several surgical conditions, involving skin, soft tissue and orthopedics and traumatology (Langley‐Hobbs, Demetriou, & Ladlow, 2014; Montavon, Voss, & Langley‐Hobbs, 2009), which justify the use of this biomaterial. However, there are a few reports of the PRF application in cats (Soares et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These animals were tested negative for Leishmania infantum and Dirofilaria immitis , had a regularly updated vaccine and deworming schedule, and lived mostly indoors and without a traveling record. Each PRF clot was produced as described in previous works [ 16 , 18 ]. Briefly, after local trichotomy of the area and skin cleansing, 5 mL of whole blood was collected to sterilized conical base polypropylene tubes (57 × 15.3 mm), without clot activator.…”
Section: Methodsmentioning
confidence: 99%
“…The success of PRF in the human clinical context has been supported by both in vitro and in vivo scientific research [ 2 , 12 , 13 , 14 , 15 ]. The increasing interest in platelet-based therapies has contributed to the development of novel veterinary treatments [ 16 , 17 ]. A recent in vitro study conducted by the authors of the present work also demonstrated the burst of PDGF-BB, TGF-ß1, VEGF-A, and interleukin-8 concentration released from both canine and feline intact PRFs over 10 days [ 18 ].…”
Section: Introductionmentioning
confidence: 99%